2006
DOI: 10.1021/ac052267s
|View full text |Cite
|
Sign up to set email alerts
|

Direct-Write Fabrication of Functional Protein Matrixes Using a Low-Cost Q-Switched Laser

Abstract: We report the use of an inexpensive, small, and "turn-key" Q-switched 532-nm Nd:YAG laser as a source for nonlinear, direct-write protein microfabrication. In this approach, microJoule pulses (pulse widths, approximately 600 ps) are focused using high numerical aperture optics to submicrometer focal spots, creating instantaneous intensities great enough to promote multiphoton excitation of a photosensitizer and subsequent intermolecular cross-linking of protein molecules. By scanning the femtoliter focal volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
78
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 15 publications
2
78
1
2
Order By: Relevance
“…Taken together, these results imply that a broad range of hydrogel swelling profiles will be possible by judicious selection [or engineering (37)] of protein building blocks. Further, protein matrices composed of avidin, which we previously have demonstrated retain biotin-binding functionality (23)(24)(25), showed attenuated swelling in acid and denaturant solutions in the biotinbound state compared with the unbound state ( Fig. 2d and Fig.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…Taken together, these results imply that a broad range of hydrogel swelling profiles will be possible by judicious selection [or engineering (37)] of protein building blocks. Further, protein matrices composed of avidin, which we previously have demonstrated retain biotin-binding functionality (23)(24)(25), showed attenuated swelling in acid and denaturant solutions in the biotinbound state compared with the unbound state ( Fig. 2d and Fig.…”
Section: Resultsmentioning
confidence: 79%
“…We and others have shown that direct-write protein matrices can retain ligand-binding and catalytic functionality similar to that of their component proteins (23)(24)(25)(26)(27), implying that native electrostatic and hydrophobic interactions governing protein conformation remain significantly intact within microstructures. However, at pH extremes, unfavorable electrostatic interactions can disrupt the native state and result in protein unfolding (31,32).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…This approach allows fabrication of functional gradients ( Figure S1) with arbitrary directionality and slope (by changing the direction and speed of the moving mask) with significantly higher resolution than other techniques that use laser scanning 8 or broadband light sources. 9 Our approach is readily adaptable to existing microscope platforms, is potentially inexpensive, 10 and should facilitate studies of cell development and differentiation.Mask-directed multiphoton lithography enables facile optimization of microfabricated materials for interfacing with cell cultures, such as the capture and incubation of motile cells. By using CAD software and an office printer it was straightforward to rapidly prototype a wide variety of bacterial microchambers, such as those shown in Figure 1C.…”
mentioning
confidence: 99%